Students' and Teacher' Perceptions on Oral Corrective Feedback Toward Students' Speaking Performance - Sirait, Jenifer Jane Patricia; Hesti Wahyuni Anggraini (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
Oral corrective feedback is an important strategy in improving students' speaking skills, but teachers and students usually have different perceptions of how feedback should be given. This discrepancy can reduce the effectiveness of feedback and slow down student progress, so this study is useful for understanding the perceptions of teachers and students. The research was conducted at Methodist High School 3 Palembang with research participants consisting of 1 teacher and 8 grade 11 students. This study used a qualitative approach by applying a case study design. Observations and interviews were conducted to identify common mistakes made by students during speaking performances and to determine the types of verbal corrective feedback most often used by teachers when providing feedback to students. In addition, interviews were conducted to explore teachers' and students' perceptions of verbal corrective feedback on students' speaking performances. Thematic analysis was used to identify the main themes in the teacher and student interviews. The results of the study show that students generally make pronunciation errors, and explicit correction is the type of oral corrective feedback most frequently used by teachers. Furthermore, both teachers and students view this positively and consider oral corrective feedback important in improving students' speaking skills.